PROSECUTOR'S AUTHORITY AS A COUNTRY LAWYER IN RETURNS OF STATE LOSSES DUE TO CORRUPTION CRIMINAL ACTION - Krisna Boboy, Rini; L. Pekuwali, Umbu; Sinurat, Aksi (RADJA PUBLIKA, 2021)
The Attorney General of the Republic of Indonesia, as one of the law enforcement agencies in Indonesia, plays an important role in the law enforcement process. The role of the prosecutor in enforcing the Law for the Maintenance of Public Order, Legal Security, and the Protection of the Interests of the State and the Civil Rights of the People, as set forth in Law No. 16 of 2014 concerning the Attorney General of the Republic of Indonesia, became known as the Prosecutor General. The role of prosecutors includes their ability to represent the state in efforts to offset financial losses incurred by the state due to criminal acts of corruption. However, this agency has not guaranteed a significant return on government losses due to corruption. The writing of this thesis uses a normative legal research methodology and serves two purposes, namely, to analyze the laws and regulations governing the authority of prosecutors as prosecutors in relation to the restitution of state losses, and to study and describe the role of prosecutors to make the restitution to guarantee government assets or to offset government losses. due to criminal acts of corruption. Therefore, it is necessary to review the existing regulations so that the existing regulations do not open opportunities for corrupters to avoid being responsible for restoring government losses. The Attorney General's Office uses an asset recovery approach that is effective, efficient, transparent, and accountable so that the recovery of state finances can be achieved for justice, certainty, and legal benefits in society.